The ORC-PD: A versatile tool for fluid selection and Organic Rankine Cycle unit design. (1st May 2016) - Pezzuolo, Alex; Benato, Alberto; Stoppato, Anna; Mirandola, Alberto
Abstract: The ORC (Organic Rankine Cycle) is an emerging and commonly accepted technology for converting medium and low temperature heat sources into electricity. Several ORC units are already in operation but there is a continuous need of new and more versatile computer tools able to perform fluid selection and plant layout optimization. For these reasons, the present work is devoted to present a computer tool able to perform the fluid selection and the plant design of ORC units maximizing, for example, the net electric power for different heat sources' type and temperature (low, medium and high temperature). The optimum fluid is selected among 81 possible candidates. The optimization is performed taking into account a wide range of operating conditions: subcritical and transcritical cycles, regenerative and non-regenerative units and heat transfer made from the hot side and the power cycle (with and without the oil loop). Being the expander a crucial component, the axial and radial efficiency prediction charts are employed to estimate the expander isentropic efficiency. An exergy and economic analysis is also performed. For the selected test case the maximum net electric power can be reached using Toluene with a recuperative subcritical cycle. Highlights: A tool for ORC unit design is presented. An energy, exergy and economic analysis have been performed. Different optimization targets can be imposed. The ORC cycle are optimized according to the heat source, the user requirement and the optimization target. Four plant configurations and 81 different organic fluids are taken into account during the optimization process.